Biogels in Soils: Plant Mucilage as a Biofilm Matrix That Shapes the Rhizosphere Microbial Habitat - Nazari, Meisam; Bickel, Samuel; Benard, Pascal; Mason-Jones, Kyle; Carminati, Andrea; Dippold, Michaela A. (Frontiers in plant science, 2022)
Mucilage is a gelatinous high-molecular-weight substance produced by almost all plants, serving numerous functions for plant and soil. To date, research has mainly focused on hydraulic and physical functions of mucilage in the rhizosphere. Studies on the relevance of mucilage as a microbial habitat are scarce. Extracellular polymeric substances (EPS) are similarly gelatinous high-molecular-weight substances produced by microorganisms. EPS support the establishment of microbial assemblages in soils, mainly through providing a moist environment, a protective barrier, and serving as carbon and nutrient sources. We propose that mucilage shares physical and chemical properties with EPS, functioning similarly as a biofilm matrix covering a large extent of the rhizosphere. Our analyses found no evidence of consistent differences in viscosity and surface tension between EPS and mucilage, these being important physical properties. With regard to chemical composition, polysaccharide, protein, neutral monosaccharide, and uronic acid composition also showed no consistent differences between these biogels. Our analyses and literature review suggest that all major functions known for EPS and required for biofilm formation are also provided by mucilage, offering a protected habitat optimized for nutrient mobilization. Mucilage enables high rhizo-microbial abundance and activity by functioning as carbon and nutrient source. We suggest that the role of mucilage as a biofilm matrix has been underestimated, and should be considered in conceptual models of the rhizosphere.